Prenatal androgen exposure predicts sexuality disorders: insights from anthropometric measurements and questionnaires - Bartoszek, Adrian; Sawic, Magdalena; Pierzchała, Karol; Kudrycka, Aleksandra; Białasiewicz, Piotr; Kuczyński, Wojciech (Frontiers in Endocrinology, 2025)
BackgroundSexual activity has been linked to various physical and psychological benefits, yet national surveys indicate a decrease in sexual engagement among American adults from the late 1990s to the early 2010s. The 2D:4D ratio, representing the relative lengths of the second and fourth digits, is commonly used as a biomarker for prenatal androgen exposure (PAE). This ratio may offer insights into the hormonal environment during fetal development, which could impact sexual attitudes and mental well-being. This study aimed to explore the associations between PAE, inferred via 2D:4D ratio, and various psychosocial factors, including sexual attitudes, mental health, and self-reported sexual satisfaction.MethodsA cohort of male and female participants was assessed for 2D:4D ratios on both hands. Questionnaires captured a range of psychosocial and sexual measures, including the Arizona Sexual Experiences Scale (ASEX), the Sexual Satisfaction Questionnaire (SSI), the Sapiosexual Questionnaire (SapioQ), the Kinsey Scale for sexual orientation, and tools assessing mental health and quality of life (SF-12, PHQ-9, GAD-7, MDQ, PSQI). Statistical analyses were conducted to identify correlations between PAE, mental health, and sexuality, with gender differences considered.ResultsWomen reported higher ASEX and SSI scores but lower SF-12 mental and physical health scores than men, consistent with smaller 2D:4D effect sizes reported in previous research. Overall, PAE did not correlate strongly with general mental health or sexual satisfaction. However, high PAE was associated with a greater openness to casual relationships, particularly among women, while low-PAE individuals prioritized intelligence over physical traits in partner preferences.ConclusionsThese findings suggest that PAE, as measured by the 2D:4D ratio, may be associated with certain adult psychosocial traits. Although correlations were weak, this study contributes to understanding the subtle role of PAE in shaping sexual attitudes and mental health, highlighting the need for further research in more diverse populations.